(untitled) (Revista de Ciências Agroveterinárias, 2019)
Genetic gain for final weight and influence of selective breeding on several zootechnical and morphometric parameters of selected Nile tilapia within different genetic groups, after one generation of individual selection, were evaluated. After selection, five genetic groups were sampled for current analysis. Ten separate matings were carried out in 50 m² fish ponds for five selected groups and five non-selected groups (sampled fish with mean weight of the same genetic groups for control). Thirty females from each genetic group were mated with twelve males, totaling 300 females and 120 males. Larvae from ponds were collected after 21 days, from which 500 larvae were sampled per genetic group, with hatchery in ten 100L tanks, separately for each group, followed by rearing in ten 1 m³ hapas in a 300 m² fish pond. Afterwards, 30 tilapias (30.0±1.6 g) from each genetic group, totaling 300 animals, were tagged with magnetic transponder. These were distributed into three 50 m² ponds with ten animals of each group per fish pond. After 140 days of rearing, the animals were harvested for evaluation. Individual selection was characterized by final and fillet weight gain, respectively at 8.4% and 9.5%. In addition, the results showed an increase in total length, standard length, body height, body width and corrected length. However, no modifications occurred in parameters such as survival rate, carcass yield, fillet yield, and head length by final weight selection.